Accounting discretion of banks during a financial crisis - Laeven, Luc.; Huizinga, Harry (Washington, D.C. : International Monetary Fund, 2009)
This paper shows that banks use accounting discretion to overstate the value of distressed assets. Banks' balance sheets overvalue real estate-related assets compared to the market value of these assets, especially during the U.S. mortgage crisis. Share prices of banks with large exposure to mortgage-backed securities also react favorably to recent changes in accounting rules that relax fair-value accounting, and these banks provision less for bad loans. Furthermore, distressed banks use discretion in the classification of mortgage-backed securities to inflate their books. Our results indicate that banks' balance sheets offer a distorted view of the financial health of the banks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet